2010
DOI: 10.1111/j.2042-3306.2010.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intensive exercise on plasmatic neutrophil elastase level in eventing and endurance horses

Abstract: Summary Reasons

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 39 publications
4
16
0
Order By: Relevance
“…Our study highlighted that after an endurance race, active MPO is present in horse skeletal muscle and that its activity increases in association with an increase of plasma CK, a witness of muscle damage. These results are to be connected to recent studies which demonstrated that the concentration of 2 inflammatory markers, MPO and elastase, increased both in plasma and muscle in correlation with an increase of the plasmatic CK levels after an endurance race in horses (Lejeune et al . 2010; Serteyn et al .…”
Section: Discussionsupporting
confidence: 75%
“…Our study highlighted that after an endurance race, active MPO is present in horse skeletal muscle and that its activity increases in association with an increase of plasma CK, a witness of muscle damage. These results are to be connected to recent studies which demonstrated that the concentration of 2 inflammatory markers, MPO and elastase, increased both in plasma and muscle in correlation with an increase of the plasmatic CK levels after an endurance race in horses (Lejeune et al . 2010; Serteyn et al .…”
Section: Discussionsupporting
confidence: 75%
“…Results of the present study confirm earlier findings of increased post exercise circulating neutrophil numbers and MPO and ELT concentrations in endurance horses (Art et al . 2006; Lejeune et al . 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Further, increased levels of circulating MPO and ELT have been shown to occur in the post exercise period (Art et al . 2006; Lejeune et al . 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Augmented levels of the protease inhibitors α1-AT and α1-AT-RP may contribute to suppress elastase activity and indirectly inhibit elastase-related complement activation [72]. This protease increases after intense exercise in horse [43,73] as well as during airway inflammation [74], which often develops during prolonged movement and training [75][76][77]. Moreover, high levels of α1-AT have been found after intensified training in equine muscle biopsy [38].…”
Section: 2mentioning
confidence: 98%